2021
DOI: 10.3390/jcm10225270
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers and Thromboembolic Risk in Patients with Non-Muscle-Invasive Bladder Cancer

Abstract: Introduction: Patients with bladder cancer have a high risk of venous thrombosis that represents a key challenge for physicians in the decision-making for initiating anticoagulation therapy. Non-muscle-invasive bladder cancer (NMIBC) represents more than 70% of all diagnosed bladder malignancies; therefore, we aimed to evaluate the relationship of the neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), and risk of thrombosis by using the International Medical Prevention Registry on Venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Its increased levels were proposed, by Xiong et al, as a risk biomarker for thrombotic complications following surgery [ 49 ]. Monocyte to lymphocyte ratio (MLR) is a simple index that is mainly related to inflammatory activation, however increased thrombotic risk was also postulated [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its increased levels were proposed, by Xiong et al, as a risk biomarker for thrombotic complications following surgery [ 49 ]. Monocyte to lymphocyte ratio (MLR) is a simple index that is mainly related to inflammatory activation, however increased thrombotic risk was also postulated [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, research has primarily focused on in ammatory markers derived from complete blood count (CBC) parameters, such as neutrophils (N), monocytes (M), lymphocytes (L), platelets (P), albumin (ALB), hemoglobin (Hb), platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and systemic immune-in ammation index (SII). These markers have demonstrated predictive effects on the survival and prognosis of malignant tumors, including colorectal cancer [22], gastric cancer [23], breast cancer [24][25][26], lung cancer [27][28], rectal cancer [29], ovarian cancer [30], bladder cancer [31], neurological diseases [32], and oral cancer [33]. Multiple lines of evidence suggest that radiation enteritis is an in ammatory reaction [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies (19)(20)(21)(22)(23)(24) have reported the impact of RE, such as on the distribution characteristics of intestinal ora, and signi cant changes in fecal metabolites are closely related to the severity of RE during RT. In the past 10 years, research has focused on the in ammatory markers of complete blood count (CBC)-derived parameters such as neutrophils (N), monocytes (M), lymphocytes (L), platelets (PLT), albumin (ALB), hemoglobin (Hb), platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and systemic immune-in ammation index (SII), which have predictive effects on the survival and prognosis of malignant tumors, such as CC (25), gastric cancer (26), breast cancer (27)(28)(29), lung cancer (30,31), rectal cancer (32), ovarian cancer (33), bladder cancer (34), neurological diseases (35), and oral cancer (36). Multiple lines of evidence have suggested that RE is an in ammatory reaction (37)(38)(39)(40)(41).…”
mentioning
confidence: 99%